Acquisition and reversal of visual discrimination learning in APPSwDI/Nos2−/− (CVN) mice. (22nd May 2017) - Piiponniemi, Tuukka O.; Bragge, Timo; Vauhkonen, Eveliina E.; Vartiainen, Petra; Puoliväli, Jukka T.; Sweeney, Patrick J.; Kopanitsa, Maksym V.
Graphical abstract: Highlights: CVN mice acquired Visual Discrimination at a rate comparable to that of WT mice. Reversal of Visual Discrimination learning in CVN mice was slower than in WT mice. CVN mice made more errors during the Reversal of Visual Discrimination learning. CVN mice were slower to collect liquid food reward. Abstract: Studies of cognitive behavior in rodent models of Alzheimer's disease (AD) are the mainstay of academic and industrial efforts to find effective treatments for this disorder. However, in the majority of such studies, the nature of rodent behavioral tests is considerably different from the setting associated with cognitive assessments of individuals with AD. The recently developed touchscreen technique provides a more translational way of rodent cognitive testing because the stimulus (images in different locations on the screen) and reaction (touch) are similar to those employed in human test routines, such as the Cambridge Neuropsychological Test Automated Battery. Here, we used Visual Discrimination and Reversal of Visual Discrimination touchscreen tasks to assess cognitive performance of APPSwDI/Nos2 −/− (CVN) mice, which express mutated human APP and have a homozygous deletion of the Nos2 gene. We revealed that CVN mice made more first-time errors and received more correction trials than WT mice across both discrimination and reversal phases, although mutation effect size was larger during the latter phase. These results indicate sensitivity of touchscreen-based measurements to AD-relevant mutations in CVN mice and warrant future touchscreen experiments aimed at evaluating other cognitive and motivational phenotypes in this AD mouse model.